NorCPM1 and its contribution to CMIP6 DCPP - I. Bethke (Copernicus Publications, 2021)
The Norwegian Climate Prediction Model version 1 (NorCPM1) is a new research tool for performing climate reanalyses and seasonal-to-decadal climate predictions. It combines the Norwegian Earth System Model version 1 (NorESM1) – which features interactive aerosol–cloud schemes and an isopycnic-coordinate ocean component with biogeochemistry – with anomaly assimilation of sea surface temperature (SST) and T/S<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="21pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="29d882486804d5f067bbf3ffd749abef"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gmd-14-7073-2021-ie00001.svg" width="21pt" height="14pt" src="gmd-14-7073-2021-ie00001.png"/></svg:svg>-profile observations using the ensemble Kalman filter (EnKF).